Regression Discontinuity Design with Continuous Measurement Error in the Running Variable - Laurent Davezies; Thomas Le Barbanchon (Institute of Labor Economics (IZA), 2017)
Since the late 90s, Regression Discontinuity (RD) designs have been widely used to estimate Local Average Treatment Effects (LATE). When the running variable is observed with continuous measurement error, identification fails. Assuming non-differential measurement error, we propose a consistent nonparametric estimator of the LATE when the discrepancy between the true running variable and its noisy measure is observed in an auxiliary sample of treated individuals, and when there are treated individuals at any value of the true running variable – two-sided fuzzy designs. We apply our method to estimate the effect of receiving unemployment benefits.
Keywords: C21; C14; C51; 330; regression discontinuity design; measurement error